Using group work to improve generic skills of management accounting students in preparation for their accounting careers / Moonsamy Naidoo - Naidoo, Moonsamy (Faculty of Accountancy, 2014)
This study examines the views of undergraduate management accounting students on their generic skills that were improved and those that require improvement before and after a group assignment. The study also sought to assess whether an effective leader resulted in positive group outcomes. This paper replicates parts of the paper of Dyball et al. (2007) that focused on the perceptions of students on the usefulness of assessed group work and whether the assessed group work was effective in transferring team skills. Data in this study were collected via questionnaires completed by 218 Management Accounting students enrolled in the course as part of their undergraduate studies in a Bachelor of Business degree at a Victorian university in Australia. The current study finds that group assessments can be used as an alternative to traditional assessments in Management Accounting. Students felt that group assessments were a break from formal tests and reduced their workloads as they share the tasks and could respond with better quality outputs. Students viewed group assessments as enabling them to be challenged, discuss different views and interact better to achieve more positive outcomes. The study also examines methods to improve work and to develop the role of group leaders further to ensure positive group outcomes.